2017
DOI: 10.1111/jhn.12502
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the nutritional composition and cost of gluten‐free versus regular food products in the UK

Abstract: Differences exist in the nutritional composition of GF and regular food. GF food is unlikely to offer healthier alternatives to regular foods, except for those who require a GF diet for medically diagnosed conditions, and it is associated with higher costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
116
3
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 34 publications
15
116
3
14
Order By: Relevance
“…However, the low positive predictive value of celiac antibodies in this study highlights the short‐coming of this strategy. Therefore, duodenal biopsy is still required to avoid misdiagnosis and prevent patients from being unnecessarily subjected to a gluten‐free diet that significantly increases food costs and reduces food choice in patients that already have many restrictions in place due to their diabetes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the low positive predictive value of celiac antibodies in this study highlights the short‐coming of this strategy. Therefore, duodenal biopsy is still required to avoid misdiagnosis and prevent patients from being unnecessarily subjected to a gluten‐free diet that significantly increases food costs and reduces food choice in patients that already have many restrictions in place due to their diabetes …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, duodenal biopsy is still required to avoid misdiagnosis and prevent patients from being unnecessarily subjected to a gluten-free diet that significantly increases food costs and reduces food choice in patients that already have many restrictions in place due to their diabetes. 41,42 The strengths of the study include a large sample size, screening with three different celiac antibody tests, and exclusion of IgA deficiency as a confounder. The limitations of this study include its cross-sectional design, the lack of control subjects, the dropout rate, and absence of genetic test results.…”
Section: Discussionmentioning
confidence: 99%
“…Gluten free market has expanded in the past years mainly in the developed world, such as UK and US, with different nutrition values, in comparison with other food products, such as higher amount of fat and also it has been confirmed that it is significantly in higher costs too [26]. In the current study, we have looked at different costs (Figure 1), where results have demonstrated that cost of drinks were significantly lower than snacks, staple foods and additives.…”
Section: Food Costs Of Prebiotics Probiotics and Gluten Free Types Omentioning
confidence: 99%
“…Conversely, research on the cost or nutritional value of GFPs has been carried out, although usually focused on the products available in a single country with a reduced number of breads or brands analyzed. These studies were conducted in Italy (Mazzeo, Cauzzi, Brighenti, & Pellegrini, ; Morreale, Angelino, & Pellegrini, ), Austria (Missbach et al., ), Spain (Matos & Rosell, ; Miranda, Lasa, Bustamante, Churruca, & Simon, ), the United Kingdom (Allen & Orfila, ; Fry, Madden, & Fallaize, ), Brazil (do Nascimento et al., , ), Australia (Wu et al., ), or Canada (Kulai & Rashid, ).…”
Section: Introductionmentioning
confidence: 99%